Necessidades de informação para os turistas: estudo de caso do município de Tiradentes - MG - Leonardo Pellegrino de Souza (2000)
This thesis was developpeci to dentify wich kind of data and information about touristic attractions must be part of an information service or product created to satisfyed their interess and necessities. We studied, first, the methodology for touristic information description and representation, proposed by EMBRATUR (the Brazilian governmental organization responsible for aspect involving the touristic industry). Next we identified, through interviews, the information about tounstic atractions that tourists need / want to know. Finally, we propose some refencial criteria about me touristic information that should be part of an information service or product. The research was conducted in Tiradentes, a historical city located at the State of Minas Gerais, Brazil. Thirty-two tourists were interviewed and their answers were analized. The subjects responded questions about their information needs on four touristic categories: natural attractions, historical and cultural attractions, traditional and popular public demonstration and uses, and programmed events. The information needed by the touristics we classified into minimal and recommended. The criteria for descripetions of tounstic atractions, sugested by this study, could be used in me elaboration of touristic information products and services.